The Utilization of Kecondang (T. leontopetaloides) in Karimunjawa Island as Alternative Food - Lestari Sihotang, Vera Budi (Proceeding International Conference on Global Resource Conservation, 2013)
Research about the utilization of kecondang (T. leontopetaloides) in Karimujawa Island is done. The utilization is done by people in three islands namely Genting Island, Nyamuk Island, and Kemujan Island. Field trip and in depth interview method are done to collect data. Any uses of kecondang are practiced directly. The knowledge of this utilization obtained from generation to generation and has been developed until now. Most of people use kecondang as alternative food such as cookies and porridge.Â Keywords: alternative food, kecondang, Genting Island, Karimunjawa Island, Kemujan Island, Nyamuk IslandÂ